Response to Different Oxygen Partial Pressures and Evolution Analysis of Apoptosis-Related Genes in Plateau Zokor (Myospalax baileyi) - An, Zhifang; Chen, Xiaoqi; Li, Jimei (Frontiers in Genetics, 2022)
The plateau zokor, Myospalax baileyi, is a native species of the Qinghai-Tibet Plateau, which spend its entire life underground in sealed burrows. P53 is a master regulator of cell death by inducing apoptosis, it has numerous apoptotic target genes, as with p53-induced protein with a death domain (PIDD), p53-upregulated modulator of apoptosis (PUMA), insulin-like growth factor binging protein 3 (IGFBP3), and apoptosis protease-activating factor 1 (Apaf-1). To investigate the sequence characteristics of apoptotic target genes and the response to different oxygen partial pressures (pO2) in plateau zokor and SD rat, we analyzed the sequences of the homology and the convergent evolution sites and measured the expression levels under 14.13 kPa (3300 m) and 16.12 kPa (2260 m). Our results showed that, (1) the sequences of the apoptotic target genes in plateau zokor had highly homologies with Nannospalax galili, followed by the Rattus norvegicus; (2) PIDD, PUMA, IGFBP3 and Apaf-1 of plateau zokor occurred five, one, two and five convergent sites in the functional domains with Nannospalax galili, respectively. (3) under low pO2, the expression level of PIDD was the high level in liver and skeletal muscle, and down-regulated in lung of plateau zokor, and up-regulated of IGFBP3 and Apaf-1 in liver, lung and skeletal muscle, and up-regulated of PUMA in skeletal muscle of plateau zokor. In SD rat, under low pO2, down-regulated of PUMA and Apaf-1 in liver, down-regulated of IGFBP3 and PUMA in lung and skeletal muscle, respectively. Compared to the SD rat, the expression patterns of Apaf-1, IGFBP3 and PUMA were reversed in liver, lung and skeletal muscle of plateau zokor, respectively. In conclusion, for the long-time adaptation to the hypoxic environments, PIDD, PUMA, IGFBP3 and Apaf-1 of plateau zokor occurred the convergent evolution, and we speculated that the convergent evolution sites may up-regulated the levels under low oxygen partial pressures to induce apoptosis in tissues of plateau zokor, so as to suppression of tumorigenesis under hypoxic environments.